Catherine M. Wilfert Oral History Interview, 2006 - Wilfert, Catherine M. (2006)
Dr. Catherine Wilfert discusses family support; her decision to become a physician; her medical degree from Harvard; the atmosphere for women at Harvard; the differences between the Harvard and Duke campuses; scientific collaborations on Duke campus; people in Department of Pediatrics; working with Dr. Rebecca Buckley on Rocky Mountain Spotted Fever cases; practicalities of working in the lab; the welcoming nature of the Duke Pediatrics Department towards women; the names of important women in the medical center; her husband, Dr. Samuel Katz; the direction of Department of Pediatrics under Dr. Katz's leadership; institutional support for the Department of Pediatrics; differences between pediatric medicine and internal (adult) medicine; physicians' reactions to first hearing about AIDS in the 1980s; patients' deaths due to AIDS; Duke's involvement in clinical trials to treat AIDS; Dr. Dani Bolognesi; her own involvement in giving AZT to mothers; the dramatic reduction of newborn AIDS patients due to AZT use by infected mothers; publicity of the initial trial; controversies of the Thailand trial; her personal stand about early international trials with AZT; the entities responsible for international AZT trials; differences between treating patients in the United States and in developing countries; the dramatic decrease in newborn AIDS patients in United States; difficulties of treating AIDS patients in developing countries; the necessity of treating AIDS patients in developing countries, even by imperfect means; her personal passion for the cause of treating AIDS patients in developing countries; her work for the Elizabeth Glaser Pediatric AIDS Foundation; her retirement from Duke; the foundational support for her work; the need for financial support in the cause of fighting AIDS; countries on which she focuses the most; her travel schedule; working with national governments of developing countries; the status of pediatric AIDS in the United States; specific cases (not identified by name) that stand out to her; others who are in the fight against AIDS; what Westerners should know about the AIDS struggle in the developing world; dissatisfaction with current system of medical care delivery in the United States; her role as chief of the Division of Infectious Diseases; and interactions with Dr. Katz as chief under his chairmanship. The transcription of this interview was made possible by a grant from the Josiah Charles Trent Memorial Foundation.